2015
DOI: 10.1007/s12094-015-1313-z
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic features of primary tumor as independent predictive factors for lymph node metastasis in papillary thyroid carcinoma

Abstract: Preoperative sonographic features of primary tumor including the number, size and coexistence of HT were independent predictive factors for the state of cervical lymph node metastasis in patients with papillary thyroid carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 23 publications
0
24
0
1
Order By: Relevance
“…The main characteristics of the 71 articles included in this meta-analysis are summarized in Table 1 [ 7 8 9 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 78 ]. A total of 44,034 participants with PTC were enrolled, of whom 11,132 (25.3%) had HT.…”
Section: Resultsmentioning
confidence: 99%
“…The main characteristics of the 71 articles included in this meta-analysis are summarized in Table 1 [ 7 8 9 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 78 ]. A total of 44,034 participants with PTC were enrolled, of whom 11,132 (25.3%) had HT.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have been proposed for the LNM risk assessment of PTC patients. Some manifested that tumor size, tumor location, tumor extension, microcalcifications, and Hashimoto's disease are independent risk factor of LNM 9,[15][16][17][18] . Some combined the above risk factors with blood markers such as thyroid stimulating hormone (TSH) and antithyroglobulin antibodies (TGAb) to construct LNM prediction models for PTC patients 19,20 .…”
mentioning
confidence: 99%
“…Accurate evaluation of CLNM prior to surgery is important for determining appropriate extent of lymph node dissection. A considerable body of literature shows that male gender, age of onset < 45 y, tumor size > 81.0 cm, and multifocality are associated with higher rate of CLNM in PTC [ 3 , 4 , 15 17 ]. Considering the impact of gender on the clinicopathological features of PTC, it is necessary to explore whether the predictive factors of CLNM differ by gender.…”
Section: Discussionmentioning
confidence: 99%
“…Preoperation risk of CLNM is important for deciding extent of surgery. Recent studies focused on the predictive risk factors for CLNM have revealed that age of onset, size of tumor, and multifocality are independently associated with CLNM in PTC [ 15 , 17 , 23 ]. It has been established that age is negatively correlated with CLNM in PTC, and the risk of CLNM increases proportionally with the number of tumor foci [ 15 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation